Okręgowy Szpital Koni nr 4 w Łodzi w latach 1918–1926 - Jarno, Witold (Zeszyty Wiejskie, 2016)
The article describes the history of the military hospital for horses in Lodz, which existed in the years 1918–1926. The hospital was created in November 1918 on the basis of a German hospital for horses, which existed in Lodz during the First World War. The first commander of the Military Hospital for Horses in Lodz was Cpt. veterinarian Stanislav Iwaszkiewicz, appointed to this post in March 1919. The second commander of this hospital was major veterinarian Kazimierz Bortnowski, occupying this post from the summer of 1921 until the end of 1924 (in the meantime promoted to lieutenant colonel). The last commander was major veterinarian Eugene Świecki, who managed the work of this hospital from February 1925 to the time of liquidation of the hospital in August 1926. The sick horses were treated in this hospital and afterwards healthy horses could return to military units. It was a very important task because in the years of the Second Republic almost all the military transport was based on horses. For this reason a good condition of these animals largely affected the ability of a combat army.